Un intricato processo ad Atene: Eufileto uccide Eratostene, seduttore della moglie (Lysias, Or. I: De Eratosthenis caede apologia) - Bologna, Orazio Antonio (Vox Patrum, 2011)
In Athens in the late and early fifth century B.C. Eratosthenes, a well-known real Don Juan was killed. He sets his eyes on a young wife and seduces her, she is the wife of Euphiletus, a modest farmer, who spent a lot of time in countryside, away from his wife. Euphiletus, after the birth of his (first) son, places full faith in his wife. Having been informed about the affair, he catches her in adultery and, in front of some witnesses, kills Eratosthenes. The victim’s relatives hold a trial against the murderer, who before the Court gives a brilliant oration, written by Lysia one of the greatest orators of Athens.